Numerical simulation of a wave energy converter using linear generator - Ba, Dang The (Vietnam Journal of Mechanics, 2013)
This paper presents results of numerical simulation for a wave energy converter using linear permanent magnet generator. The use of linear permanent generator has advantages of simple structure, minimizing mechanical loose... On the base of mechanics model, a system of equations describing the operation of the device under linear potential wave was obtained. The magnetic field in generator was calculated by Flex-PDE software. The system of movement equations was numerically solved with Matlab.Various calculations were performed with different parameters of wave conditions and device’s structures to determine the device’s configuration for a 300 W output power for the offshore wave condition in South-Central offshore of Vietnam. The results also show potential of developing the wave energy conversion to meet the energy demand in some coastal and island regions of Vietnam.